Magnetic switching of Kerker scattering in spherical microresonators - G. P. Zouros; K. L. Tsakmakidis; G. D. Kolezas; E. Almpanis; BASKOURELOS, K.; Stefański, T.P. (Nanophotonics, 2020)
Magneto-optical materials have become a key tool in functional nanophotonics, mainly due to their ability to offer active tuning between two different operational states in subwavelength structures. In the long-wavelength limit, such states may be considered as the directional forward- and back-scattering operations, due to the interplay between magnetic and electric dipolar modes, which act as equivalent Huygens sources. In this work, on the basis of full-wave electrodynamic calculations based on a rigorous volume integral equation (VIE) method, we demonstrate the feasibility of obtaining magnetically-tunable directionality inversion in spherical microresonators (THz antennas) coated by magnetooptical materials. In particular, our analysis reveals that when a high-index dielectric is coated with a magnetooptical material, we can switch the back-scattering of the whole particle to forward-scattering simply by turning off/ on an external magnetic field bias. The validity of our calculations is confirmed by reproducing the above two-state operation, predicted by the VIE, with full-wave finite-element commercial software. Our results are of interest for the design of state-of-the-art active metasurfaces and metalenses, as well as for functional nanophotonic structures, and scattering and nanoantennas engineering. © 2020 Grigorios P. Zouros et al., published by De Gruyter. This work is licensed under the Creative Commons Attribution 4.0 International License.
cited By 0